Low-carbon cement-based ultra-high-performance concrete with electromagnetic wave absorbing function and preparation method of low-carbon cement-based ultra-high-performance concrete

By modifying the micro powder of construction waste and combining components such as ferrosilicon absorbing micro powder, the problem of taking into account the density and carbonization effect in low-carbon cement-based ultra-high performance concrete is solved, and efficient use of materials and the granting of electromagnetic wave absorption functions are achieved.

CN119528507APending Publication Date: 2025-02-28HUAXIN CEMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652688.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to take into account high density and low carbonization effects in low-carbon cement-based ultra-high performance concrete, and at the same time, it effectively utilizes construction waste micro powder, and the material lacks electromagnetic wave absorption function.

Method used

By acidolysis, co-precipitation and alkaline activity activation treatment of construction waste micro powder, it is converted into calcium-aluminum hydrotalcite, and its hydration activity is improved; combined with ferrosilicon absorption micro powder and hydration enhancement components, the carbonization process of cement is adjusted, and retarding components and water-reducing components are added to improve the over-viscosity problem of the slurry and increase the CO2 absorption efficiency.

Benefits of technology

It realizes the high density and good mechanical properties of low-carbon cement-based ultra-high performance concrete, while improving the electromagnetic wave absorption performance and CO2 storage rate of the material, enhancing the resource utilization of micro powder in construction waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528507A_ABST
    Figure CN119528507A_ABST
Patent Text Reader

Abstract

The invention discloses low-carbon cement-based ultra-high performance concrete with an electromagnetic wave absorbing function. The low-carbon cement-based ultra-high performance concrete is prepared from the following components in parts by weight: 350 to 450 parts of low-carbon cement, 450 to 550 parts of hydration enhancing component, 150 to 250 parts of ferrosilicon wave absorbing micro powder, 100 to 200 parts of modified regenerated construction waste micro powder, 1100 parts of ferrosilicon fine aggregate, 1.0 to 2.0 parts of retarding component, 10.0 to 12.5 parts of water reducing component and 190 to 210 parts of water, steel fibers accounting for 1.5-2.5% of the volume of the low-carbon cement-based ultra-high performance concrete with the electromagnetic wave absorbing function are externally doped; the modified regenerated construction waste micro powder is obtained by carrying out acidolysis, coprecipitation and alkali activity excitation on construction waste micro powder; the expansion degree of the obtained product is larger than or equal to 600 mm, the 28d compressive strength can reach 110 MPa or above, the chloride ion permeability resistance coefficient can be smaller than 19.0 * 10 <-14 > m < 2 >. S <-1 >, the CO2 storage rate in the preparation process can reach 20% or above, the defect that slurry is too sticky due to high adsorbability of regenerated construction waste micro powder is overcome by adding the wave-absorbing component, and the service life of the product is prolonged. Meanwhile, the low-carbon cement-based ultra-high performance concrete has an electromagnetic wave absorbing function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and in particular relates to a low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function and a preparation method thereof. Background Art

[0002] At present, the preparation of ultra-high performance concrete usually uses ordinary Portland cement and / or Portland cement as the main cementitious material, and the main mineral composition of ordinary Portland cement and / or Portland cement is C2S, C3S, C3A, C4AF, and the main calcium source of these mineral compositions is limestone, which produces a large amount of CO2 when decomposed at high temperature. Low-carbon cement is a cement product that can significantly reduce carbon emissions. Its carbon dioxide emissions during the production process are 40%-80% lower than those of ordinary cement. Commonly used raw materials include steel slag, fly ash, slag and silicate, and the main mineral composition is 5%-40% C3S2, 20%-50% C2S, and 10%-50% CS. If low-carbon cement can be used to prepare ultra-high performance concrete, it will have very important environmental significance.

[0003] However, although low-carbon cement production has lower carbon emissions, its own hydration activity is low, and the products need to be carbonized to be enhanced. During the carbonization process of low-carbon cement products, the denser the product, the worse the carbonization enhancement effect. However, the preparation of ultra-high performance concrete often requires the product to have a higher density in order to have excellent mechanical properties, durability and toughness. Therefore, when using low-carbon cement for the preparation of ultra-high performance concrete, how to balance the carbonization effect of low-carbon cement and the high density requirements of ultra-high performance concrete is an urgent problem to be solved.

[0004] At the same time, construction waste powder is an issue that cannot be ignored when recycling waste concrete. It accounts for about 5%-20% of the total amount of waste concrete. Its main mineral components are silicon dioxide, calcium hydroxide, calcium sulfonate, calcium aluminosilicate and other potentially active components. However, when construction waste powder is used in concrete preparation, especially ultra-high performance concrete with a low water-binder ratio (usually 0.14-0.22), due to the high water absorption rate and low hydration activity of construction waste powder, the workability of the mixture is poor when concrete is prepared with construction waste powder, and the mechanical properties and durability after hardening are also poor, which greatly limits its resource utilization. If construction waste powder can be successfully used in the preparation of ultra-high performance concrete, it will not only provide a new direction for the resource utilization of construction waste powder, but also increase the low-carbon emission reduction significance of ultra-high performance concrete.

[0005] In addition, with the rapid development of science and technology, information dissemination using electromagnetic waves as carriers has penetrated into all areas of people's lives. While electronicization, informatization and high technology make people's lives more convenient, they also make people face serious electromagnetic radiation pollution, wireless communication security issues, signal interference issues, and sometimes even lead to the leakage of national political and military information. As a building material with increasingly wide applications, if UHPC can be given electromagnetic wave absorption function, it will be of great significance for its promotion and application in the field of electromagnetic shielding. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function. While ensuring the high density requirement of the ultra-high performance concrete, the carbonization effect of low-carbon cement is taken into account, and the resource utilization of construction waste powder can be realized. By adding absorbing components, the defect of excessive viscosity of the slurry caused by the high adsorption of recycled construction waste powder is improved, and at the same time, the low-carbon cement-based ultra-high performance concrete obtains electromagnetic wave absorption function.

[0007] In order to achieve the above purpose, the technical solution is as follows:

[0008] A low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function, comprising the following components by weight:

[0009] 350-450 parts of low-carbon cement, 450-550 parts of hydration enhancing component, 150-250 parts of ferrosilicon absorbing powder, 100-200 parts of modified recycled construction waste powder, 1100 parts of ferrosilicon fine aggregate, 1.0-2.0 parts of retarding component, 10.0-12.5 parts of water reducing component, 190-210 parts of water; steel fiber accounting for 1.5-2.5% of the volume of the low-carbon cement-based ultra-high performance concrete with electromagnetic absorbing function is added; the modified recycled construction waste powder is obtained by acid hydrolysis, coprecipitation and alkali activity activation of construction waste powder.

[0010] The present invention converts unstable hydration products in the construction waste micropowder into calcium aluminum hydrotalcite with strong adsorption characteristics through acid hydrolysis, coprecipitation and alkali activity stimulation treatment of the construction waste micropowder, and stimulates the hydration activity of the construction waste micropowder, and cooperates with the hydration enhancement component to make up for the low hydration activity of low-carbon cement and ferrosilicon absorbing micropowder, resulting in low strength of the prepared low-carbon ultra-high performance absorbing concrete. At the same time, the present invention adjusts the cement enhancement component and modifies the hydration process of the recycled construction waste micropowder by adding a retarding component, and cooperates with the modified calcium aluminum hydrotalcite in the recycled construction waste micropowder, so as to provide sufficient carbonization channels for the low-carbon cement while ensuring that the prepared low-carbon absorbing UHPC has good working performance, so as to absorb more CO2 and improve the mechanical properties of the prepared low-carbon absorbing UHPC. Moreover, the present invention uses ferrosilicon absorbing powder as the absorbing component, which can be used as a filler to fill the pores of the slurry during the cement hydration process while absorbing electromagnetic waves, release free water in the pores, and improve the problem of excessive viscosity of the slurry caused by the high adsorption of modified recycled construction waste powder, thereby affecting its CO2 absorption efficiency, providing favorable conditions for the strength enhancement of low-carbon absorbing UHPC. In addition, the present invention reasonably adjusts the dosage ratio of each component, so that the carbonation of low-carbon cement and the hydration of ordinary silicate cement / silicate cement develop synergistically, further improving the mechanical properties of the entire system.

[0011] Optionally, the ferrosilicon absorbing powder is compounded by casting stone clinker powder and iron tailings powder in a mass ratio of 1:(0.3-0.5); the specific surface area of ​​the casting stone clinker powder and the iron tailings powder is not less than 350m 2 / kg.

[0012] In the present invention, the cast stone clinker powder is obtained by ball milling the cast stone clinker, and its main components are SiO2, Fe2O3, and CaO, wherein the SiO2 content is about 30%, the Fe2O3 content is about 38%, and the CaO content is about 12%, and its mineral composition is basically in an amorphous state; the iron tailings powder is obtained by ball milling the iron tailings, and its main components are SiO2 and Fe2O3, wherein the SiO2 content is about 65%, the Fe2O3 content is about 15%, and its mineral composition is mainly quartz in a crystalline state. The present invention selects cast stone clinker powder and iron tailings powder as absorbing components. Compared with existing absorbing materials such as graphene and iron oxide, they have good compatibility with cement-based materials, will not have an adverse effect on the working performance of cement-based materials, and can even improve the working performance of cement-based materials and increase the absorption rate of UHPC slurry to CO2 gas. Moreover, the cast stone clinker powder and iron tailings powder can play a physical filling role with the hydration of cement, thereby improving the mechanical properties and durability of the product.

[0013] Optionally, the modified recycled construction waste powder is prepared by the following method:

[0014] (1) Grind the construction waste powder to a specific surface area of ​​≥300m 2 / kg, then acid hydrolyze at 50-60℃, filter and obtain Ca 2+ 、Al 3+ Solution A and solid B; in this step, the acid solution of the acid hydrolysis may preferably be 15-20% by mass of hydrochloric acid, and the mass ratio of the recycled construction waste powder to the acid solution may preferably be 1: (2-3);

[0015] (2) adding an alkaline solution to the solution A, adjusting the pH of the solution A to 10-11, carrying out a coprecipitation reaction at 80-90° C., and then crystallizing at 100-110° C., cooling, filtering, washing, and drying to obtain calcium aluminum hydrotalcite and a filtrate C; in this step, the alkaline solution may preferably be a sodium hydroxide solution, and the molar concentration of the sodium hydroxide solution may preferably be 0.1-0.2 mol / L;

[0016] (3) mixing the solid B and the filtrate C, reacting with alkali at 40-60° C. for 3-5 hours, filtering, and drying to obtain micropowder D;

[0017] (4) The calcium aluminum hydrotalcite and the fine powder D are mixed to obtain modified recycled construction waste fine powder.

[0018] The present invention uses an acid hydrolysis method to decompose the unstable hydration products in the recycled construction waste micropowder, and then uses a coprecipitation method to separate the Ca 2+ 、Al 3+ The present invention is converted into calcium-aluminum hydrotalcite, wherein the calcium-aluminum hydrotalcite, as a layered structure material, can absorb water and gas, and can not only be used as a CO2 collector, but also provide a carbonization channel for CO2, thereby providing enhanced protection for the application of low-carbon cement in ultra-high performance concrete. At the same time, the present invention makes full use of the filtrate (alkaline solution) produced by the co-precipitation reaction and the filtrate (solid B) produced by the acid hydrolysis reaction. The alkaline filtrate can stimulate the chemical activity of solid B, thereby effectively improving the reaction activity of recycled construction waste micropowder and cement, thereby effectively ensuring the mechanical properties of low-carbon ultra-high performance absorbing concrete.

[0019] Optionally, the cement reinforcing component consists of ordinary Portland cement or Portland cement and silica fume; the mass ratio of the ordinary Portland cement or Portland cement to the silica fume is 1:(0.2-0.3).

[0020] The present invention uses ordinary Portland cement or Portland cement and silica fume as reinforcing components of the entire system. The hydration rate of ordinary Portland cement or Portland cement and silica fume is faster than that of low carbon cement, which can make up for the problem that when low carbon cement is used to prepare casting concrete, the hydration activity is low, resulting in slow hardening and coagulation of the slurry and a long demolding period. In addition, the calcium hydroxide produced by the hydration of ordinary Portland cement or Portland cement can balance the overall alkalinity of the slurry, avoiding the substantial reduction of the alkalinity of the slurry due to the carbonization of the low carbon cement, which leads to rust of the steel fiber and affects the durability and conductive wave absorbing performance of the low carbon ultra-high performance absorbing concrete.

[0021] Optionally, the grade of the ordinary Portland cement or Portland cement is not less than grade 42.5.

[0022] Optionally, the water demand ratio of the silica fume is not greater than 125%, and the 28d activity index is not less than 105%.

[0023] Optionally, the ferrosilicon fine aggregate is iron tailings sand with a particle size of less than 1.18 mm, and the content of particles smaller than 0.075 mm in the iron tailings sand is less than 8%.

[0024] Optionally, the retarding component is formed by mixing sodium gluconate and tartaric acid in a mass ratio of 1:(0.1-0.3); and the water-reducing component is a polycarboxylate water-reducing agent with a water-reducing rate of not less than 25%.

[0025] Optionally, the steel fiber has a diameter of 0.18-0.22 mm, a length of 13-15 mm, and an aspect ratio of 60-70.

[0026] Optionally, the main components of the low carbon cement include 23.5-25.5% C3S2, 31.5-34.5% C2S, 19.5-22.5% CS, and 20.0-24.0% C3S by mass percentage, and the specific surface area of ​​the low carbon cement is not less than 300m 2 / kg.

[0027] The second object of the present invention is to provide a method for preparing the above-mentioned low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function, comprising the following steps:

[0028] 1) After uniformly mixing the low carbon cement, the hydration enhancing component, the ferrosilicon absorbing powder, the modified recycled construction waste powder, the fine aggregate, the retarding component, and the water reducing component, the water is added and stirred into a slurry, and then the steel fiber is added to the slurry and stirred for 1-2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor with electromagnetic absorbing function;

[0029] 2) In a closed environment, a certain amount of CO2 gas is charged into the low-carbon cement-based ultra-high performance concrete slurry precursor with electromagnetic absorbing function while stirring, and the mixture is poured, formed, demolded, and cured to obtain low-carbon cement-based ultra-high performance concrete with electromagnetic absorbing function, wherein the amount of CO2 gas charged can preferably be 4-6% of the mass of the cementitious material.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention innovatively uses low-carbon cement and construction waste powder for the preparation of ultra-high performance concrete, breaks with traditional absorbing materials, and selects cast stone clinker powder, iron tailings powder and iron tailings sand as absorbing materials. While giving ultra-high performance concrete new functions, it solves the problem that low-carbon cement and construction waste powder are difficult to use in the preparation of ultra-high performance concrete, greatly improves the environmental significance of ultra-high performance concrete, and is also conducive to its promotion and application.

[0032] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function prepared by the present invention has good working performance, mechanical properties, durability and electromagnetic wave absorption characteristics, and its expansion is ≥600mm, the 28d compressive strength can reach more than 110MPa, and the chloride ion permeability coefficient can be less than 19.0×10 -14 m 2 ·s -1 Moreover, during the entire preparation process of low-carbon cement-based ultra-high performance concrete with electromagnetic absorption function, the CO2 storage rate can reach more than 20%. At the same time, it has good electromagnetic absorption performance in a wider frequency band. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : The electromagnetic wave absorbing performance of the products obtained in Examples 1-4 was tested.

[0034] Figure 2 : The electromagnetic wave absorbing performance of the products obtained in Comparative Examples 1-4 was tested. DETAILED DESCRIPTION

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.

[0036] The specific implementation method provides a modified recycled construction waste powder:

[0037] The construction waste powder is ball-milled to a specific surface area of ​​350m 2 / kg, according to the mass ratio of 1:2, the ball-milled recycled construction waste powder was placed in 15% hydrochloric acid and acid-lyzed at 50°C. After the acid-lysate was completed, it was filtered to obtain the Ca-containing 2+、Al 3+ Solution A and solid B;

[0038] A sodium hydroxide solution with a molar concentration of 0.15 mol / L is added to solution A, the pH of solution A is adjusted to 10, a coprecipitation reaction is carried out at 85° C., and then, crystallization is carried out at 100° C., cooling, filtering, washing, and drying to obtain calcium aluminum hydrotalcite and filtrate C;

[0039] The solid B and the filtrate C were mixed, and the reaction was alkali-induced at 50°C for 3 hours, filtered, and dried to obtain micro powder D;

[0040] The calcium aluminum hydrotalcite and the powder D are mixed to obtain modified recycled construction waste powder.

[0041] Raw materials used in the specific implementation:

[0042] The main mineral composition of low carbon cement is calculated by mass percentage, including: 24.8% C3S2, 33.2% C2S, 21.0% CS, 21.0% C3S. The specific surface area of ​​the low carbon cement is 325m 2 / kg.

[0043] The cement reinforcing component is composed of P·O52.5 ordinary silicate cement and silica fume in a mass ratio of 1:0.2, the water demand ratio of the silica fume is 115%, and the 28d activity index is 118%.

[0044] The ferrosilicon microwave absorbing powder is composed of cast stone clinker powder and iron tailings powder in a mass ratio of 1:0.3. The main chemical compositions of the cast stone clinker powder and iron tailings powder are shown in Table 1. The cast stone clinker powder is obtained by ball milling cast stone clinker particles to a specific surface area of ​​400 m 2 / kg; iron tailings powder is obtained by ball milling iron tailings sand to a specific surface area of ​​750m 2 / kg or so.

[0045] Table 1

[0046] raw material <![CDATA[SiO2 / %]]> <![CDATA[Al2O3 / %]]> <![CDATA[Fe2O3 / %]]> CaO / % MgO / % Iron tailings powder 65.15 7.35 14.80 3.82 4.68 Cast stone clinker powder 30.09 7.59 37.82 11.67 2.56

[0047] The ferrosilicon fine aggregate is iron tailings sand with a particle size of less than 1.18 mm, and the content of particles less than 0.075 mm in the iron tailings sand is 7.5%, and its chemical composition is basically the same as the iron tailings fine powder in Table 1. The retarding component is a mixture of sodium gluconate and tartaric acid in a mass ratio of 1:0.2. The water-reducing component is a powdered polycarboxylic acid water-reducing agent with a water-reducing rate of 25%. The average diameter of the steel fiber is 0.20 mm, the average length is 14 mm, and the average aspect ratio is 70. Unless otherwise specified, the remaining raw materials are commercially available.

[0048] Example 1

[0049] A low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function, which comprises, by weight: 350 parts of low-carbon cement, 550 parts of hydration enhancing component, 200 parts of ferrosilicon absorbing micropowder, 150 parts of modified recycled construction waste micropowder, 1,100 parts of ferrosilicon fine aggregate, 1.5 parts of retarding component, 10.0 parts of water reducing component, 210 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function.

[0050] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function is prepared by the following method:

[0051] 1) According to the above dosage ratio, low carbon cement, cement reinforcing component, microwave absorbing powder, modified recycled construction waste powder, fine aggregate, slow setting component and water reducing component are mixed evenly, and then water is added to stir into slurry, and then steel fiber is added to the slurry and stirred for 2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor with electromagnetic absorbing function;

[0052] 2) In a closed environment, 5% of the mass of the cementitious material is charged into the low-carbon cement-based ultra-high performance concrete paste precursor with CO2 gas (concentration of 99.9%) while stirring, wherein the CO2 charging time is 90 seconds, and then the mixture is poured, formed, and demolded, and the demolded specimens are subjected to standard curing to a specified age to obtain low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function.

[0053] Example 2

[0054] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function of this embodiment comprises, by weight: 350 parts of low-carbon cement, 450 parts of hydration enhancement component, 150 parts of ferrosilicon wave absorption micropowder, 100 parts of modified recycled construction waste micropowder, 1100 parts of ferrosilicon fine aggregate, 1.0 part of retarding component, 10 parts of water reducing component, 190 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function. The preparation method is the same as that of Example 1.

[0055] Example 3

[0056] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function of this embodiment comprises, by weight: 400 parts of low-carbon cement, 500 parts of hydration enhancement component, 150 parts of ferrosilicon wave absorption micropowder, 200 parts of modified recycled construction waste micropowder, 1100 parts of ferrosilicon fine aggregate, 1.5 parts of retarding component, 12.5 parts of water reducing component, 200 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function. The preparation method is the same as that of Example 1.

[0057] Example 4

[0058] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function of this embodiment comprises, by weight: 450 parts of low-carbon cement, 500 parts of hydration enhancement component, 250 parts of ferrosilicon wave absorption micropowder, 150 parts of modified recycled construction waste micropowder, 1100 parts of ferrosilicon fine aggregate, 2.0 parts of retarding component, 12.5 parts of water reducing component, 210 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function. The preparation method is the same as that of Example 1.

[0059] Comparative Example 1

[0060] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function in this comparative example uses unmodified recycled construction waste powder, which is only ball-milled to a specific surface area of ​​350m 2 / kg, and the rest is the same as in Example 1.

[0061] Comparative Example 2

[0062] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function of this comparative example does not contain any retarding component, and the rest is the same as in Example 1.

[0063] Comparative Example 3

[0064] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function of this comparative example does not have a hydration enhancing component added, and low-carbon cement is used to replace the hydration enhancing component. The rest is the same as in Example 1.

[0065] Comparative Example 4

[0066] The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function of this comparative example uses Class I fly ash to replace ferrosilicon wave absorbing micropowder, and uses quartz sand with a fineness modulus of 1.9 to replace ferrosilicon fine aggregate, and the rest is the same as Example 1.

[0067] According to the standard specification of ultra-high performance concrete, the working performance, mechanical properties and durability performance of low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function of Examples 1-4 of the present invention and Comparative Examples 1-4 were tested, and the test results are shown in Table 2. The mass loss of the test piece between 400-900°C was tested by differential scanning calorimetry analysis, and the mass loss was recorded as the CO2 absorption amount, and the CO2 storage rate was calculated by the CO2 absorption amount and the CO2 charging amount, CO2 storage rate = CO2 absorption amount / CO2 charging amount × 100%, and the calculation results are shown in Table 2.

[0068] It can be seen from Table 2 that the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function prepared in the present invention has good working performance, its 28d compressive strength can reach more than 110MPa, and its chloride ion permeability coefficient is not more than 19.0×10 -14m 2 ·s -1 . At the same time, compared with comparative example 1, after the construction waste powder is modified in Example 1 of the present invention, the mechanical properties and durability are greatly improved, among which the 28d compressive strength is increased by 29.1%, and the flexural strength is increased by 54.9%; compared with comparative example 2, the addition of an appropriate amount of retarder in Example 1 of the present invention can greatly improve the initial working performance of the slurry after CO2 is introduced, and the addition of the retarder is beneficial to the carbonization and hardening efficiency of the slurry, and then it is beneficial to the improvement of the mechanical properties and durability of the hardened slurry, among which the 28d compressive strength is increased by 23.0%, and the flexural strength is increased by 43.4%; compared with comparative example 3, the addition of cement reinforcing components in Example 1 of the present invention can greatly improve the mechanical properties of the hardened slurry, among which the 28d compressive strength is increased by 261.0%, the flexural strength is increased by 177.8%, and the durability is also significantly improved; compared with comparative example 4, the low-carbon cement-based UHPC prepared by using low-quality ferrosilicon absorbing powder and iron tailings sand in Example 1 of the present invention is comparable to high-quality fly ash and quartz sand.

[0069] Table 2

[0070]

[0071] According to the requirements of the "Test Method for Reflectivity of Radar Absorbing Materials" (GJB 2038-1994), the electromagnetic wave absorbing performance of the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorbing function of Examples 1-4 of the present invention and Comparative Examples 1-4 was tested. The test results are as follows: Figure 1-2 shown.

[0072] Depend on Figure 1 and Figure 2It can be seen that the UHPC obtained in Examples 1-4 of the present invention has good wave absorbing performance. In the entire test frequency band, the bandwidth of Example 1 less than -10dB is 7.2GHz (10.8-18GHz), and the minimum reflectivity is -15.7dB at 15GHz; the bandwidth of Example 2 less than -10dB is 7.4GHz (10.6-18GHz), and the minimum reflectivity is -15.2dB at 18GHz; the bandwidth of Example 3 less than -10dB is 6.5GHz (11.5-18GHz), and the minimum reflectivity is -14.6dB at 16.2GHz; the bandwidth of Example 4 less than -10dB is 6.8GHz (11.2-1 8GHz), and the minimum reflectivity is -15.5dB at 14.4GHz; relative to comparative example 1, after the construction waste powder is modified in Example 1 of the present invention, the wave absorption performance of the obtained UHPC can be significantly improved, wherein the bandwidth less than -10dB in comparative example 1 is 4.2GHz (13.8-18GHz), and the minimum reflectivity is -12.0dB at 18GHz, while removing the retarder (Comparative example 2) and the cement reinforcing component (Comparative example 3) has a certain effect on the wave absorption performance of the obtained UHPC, but it is not significant; Comparative example 4 uses fly ash and quartz sand to replace the ferrosilicon wave absorbing powder and iron tailings sand in Example 1 of the present invention to prepare UHPC, and the wave absorption performance is obviously worse than that of Example 1.

[0073] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function, characterized in that The following components are included by weight: 350-450 parts of low-carbon cement, 450-550 parts of hydration enhancing component, 150-250 parts of ferrosilicon absorbing powder, 100-200 parts of modified recycled construction waste powder, 1100 parts of ferrosilicon fine aggregate, 1.0-2.0 parts of retarding component, 10.0-12.5 parts of water reducing component, 190-210 parts of water; steel fiber accounting for 1.5-2.5% of the volume of the low-carbon cement-based ultra-high performance concrete with electromagnetic absorbing function is added; the modified recycled construction waste powder is obtained by acid hydrolysis, coprecipitation and alkali activity activation of construction waste powder.

2. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The ferrosilicon microwave absorbing powder is compounded by casting stone clinker powder and iron tailings powder in a mass ratio of 1:(0.3-0.5); the specific surface area of ​​the casting stone clinker powder and the iron tailings powder is not less than 350m 2 / kg.

3. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The modified recycled construction waste powder is prepared by the following method: (1) Grind the construction waste powder to a specific surface area of ​​≥300m 2 / kg, then acid hydrolyze at 50-60℃, filter and obtain Ca 2 + 、Al 3+ Solution A and solid B; (2) adding an alkaline solution to the solution A, adjusting the pH of the solution A to 10-11, carrying out a coprecipitation reaction at 80-90° C., then crystallizing at 100-110° C., cooling, filtering, washing, and drying to obtain calcium aluminum hydrotalcite and a filtrate C; (3) mixing the solid B and the filtrate C, reacting with alkali at 40-60° C. for 3-5 hours, filtering, and drying to obtain micropowder D; (4) The calcium aluminum hydrotalcite and the fine powder D are mixed to obtain modified recycled construction waste fine powder.

4. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The cement reinforcing component consists of ordinary Portland cement or Portland cement and silica fume; the mass ratio of the ordinary Portland cement or Portland cement to the silica fume is 1:(0.2-0.3).

5. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 4, characterized in that The grade of the ordinary Portland cement or Portland cement is not less than 42.5; the water demand ratio of the silica fume is not more than 125%, and the 28d activity index is not less than 105%.

6. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The ferrosilicon fine aggregate is iron tailings sand with a particle size of less than 1.18 mm, and the content of particles less than 0.075 mm in the iron tailings sand is less than 8%.

7. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The retarding component is prepared by mixing sodium gluconate and tartaric acid in a mass ratio of 1:(0.1-0.3); and the water reducing component is a polycarboxylate water reducing agent with a water reducing rate of not less than 25%.

8. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The steel fiber has a diameter of 0.18-0.22 mm, a length of 13-15 mm, and an aspect ratio of 60-70.

9. The low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function as claimed in claim 1, characterized in that The main components of the low carbon cement include 23.5-25.5% C3S2, 31.5-34.5% C2S, 19.5-22.5% CS, and 20.0-24.0% C3S by mass percentage. The specific surface area of ​​the low carbon cement is not less than 300m 2 / kg.

10. The method for preparing the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function according to any one of claims 1 to 9, characterized in that The steps include: 1) After the low carbon cement, the hydration enhancing component, the ferrosilicon absorbing powder, the modified recycled construction waste powder, the fine aggregate, the retarding component, and the water reducing component are uniformly mixed, the water is added and stirred into a slurry, and the steel fiber is added to the slurry and continued to stir for 1-2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor with electromagnetic absorbing function; 2) In a closed environment, CO2 gas is charged into the low-carbon cement-based ultra-high performance concrete slurry precursor with electromagnetic wave absorption function while stirring, and the mixture is poured, formed, demolded, and cured to obtain the low-carbon cement-based ultra-high performance concrete with electromagnetic wave absorption function.